2017
DOI: 10.1093/mnras/stx2896
|View full text |Cite
|
Sign up to set email alerts
|

High-precision multiwavelength eclipse photometry of the ultra-hot gas giant exoplanet WASP-103 b

Abstract: We present sixteen occultation and three transit light curves for the ultra-short period hot Jupiter WASP-103b, in addition to five new radial velocity measurements. We combine these observations with archival data and perform a global analysis of the resulting extensive dataset, accounting for the contamination from a nearby star. We detect the thermal emission of the planet in both the z and K S -bands, the measured occultation depths being 699±110 ppm (6.4-σ) and 3567 +400 −350 ppm (10.2-σ), respectively. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 75 publications
9
46
0
Order By: Relevance
“…Generally, if the day side atmosphere is cloud-free at the probed pressure range and non-isothermal, we would expect to measure a wavelength-dependent brightness temperature due to spectral features. In this case, the z' band usually shows a larger eclipse depth and brightness temperature than the best-fit blackbody temperature (Delrez et al 2018, see also Fig. 5).…”
Section: Albedo Of Hat-p-32 Bmentioning
confidence: 88%
See 2 more Smart Citations
“…Generally, if the day side atmosphere is cloud-free at the probed pressure range and non-isothermal, we would expect to measure a wavelength-dependent brightness temperature due to spectral features. In this case, the z' band usually shows a larger eclipse depth and brightness temperature than the best-fit blackbody temperature (Delrez et al 2018, see also Fig. 5).…”
Section: Albedo Of Hat-p-32 Bmentioning
confidence: 88%
“…Because of a conservative upper limit on the albedo, we choose the lowest of 2890 K derived by Cartier et al (2017). The values of the planetary parameters involved in Equation 1 and 2 were taken from Delrez et al (2018). This results in a tight constraint of a 97.5% confidence upper limit of A g < 0.16, the lowest value derived in this work (see Table 4).…”
Section: Wasp-103 Bmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, we support their retrieved results for this planet. Our dilution correction is based on the K-magnitude difference from Ngo et al (2016) and Delrez et al (2018). WASP-121b was observed by Evans et al (2017) and Kovacs & Kovacs (2019) who quote 3.6 µm Spitzer secondary eclipse values.…”
Section: Discussionmentioning
confidence: 99%
“…Madhusudhan (2012) predicted that for many hot Jupiters, thermal emission measurements at these wavelengths are good discriminators between carbonrich and carbon-poor exoplanets. Whilst secondary eclipse observations conducted at z -band wavelengths have been published for 9 exoplanets 1 (Sing & López-Morales 2009;López-Morales et al 2010;Smith et al 2011;Burton et al 2012;Gillon et al 2012;Lendl et al 2013;Zhou et al 2013;Föhring et al 2013;Chen et al 2014;Delrez et al 2016;Gaudi et al 2017;Delrez et al 2018), only two studies have reported secondary eclipse observations at i -band wavelengths (Mancini et al 2013;Chen et al 2014), with the most confident detection reported at 3.7σ.…”
Section: Introductionmentioning
confidence: 99%